Resolva a seguinte equação.2^x+1 - 2^3-x= 6URGENTE POR FAVOR
Soluções para a tarefa
Respondido por
0
2^(x+1) - 2^(3-x)= 6
2*2^(x) -2³ * 2^(-x) =6
2^(x)-4 * 2^(-x) = 3
2^(2x) -4 =3*2^(x)
2^(2x) -3*2^(x) -4=0
Fazendo y=2^(x)
y²-3y-4=0
y'=[3+√(9+16)]/2 =(3+5)/2 =4
y''=[3-√(9+16)]/2 =(3-5)/2 =-1
Se y=4=2²=2^(x) ==>x=2 ´´e a resposta
Se y=-1=2^(x) ...ñ existe x possível
Perguntas interessantes
Administração,
9 meses atrás
Geografia,
9 meses atrás
Direito,
9 meses atrás
Inglês,
1 ano atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás